Titanium and Technological Problems of Its Machining - Vasilko, Karol (Manufacturing Technology Journal, 2019)
Titanium is considered to be the metal of the 21st century . A material which has small density (at least two-three times smaller than iron), plasticity, shapeability, high resistance, rigidity and longevity has been required for a long time. It is required not to loose those features at high temperatures, be non-degradable in air, river and sea water, not to be soluble in acides and lyes; at the same time, it requires to have sufficient amount in terrestrial crust. Titanium is such a material. Due to its specific qualities, its applications have been spreading into many areas such as medicine (implants), space (material for space technology), chemical facilities, ships for marine transport (resistance to acids and salts), wall hooks for climbers (low density and high rigidity), ... However, titanium mechanical features lead to new problems during its technological machining. It is necessary to apply considerably different approach in its cutting. During cutting, titanium and its alloys behave specifically and it is important to know this behaviour and use it for effective part production.
Keywords: machining; titanium alloys; turning; grinding